Efforts to Increase the Creativity of Group B Children Through Project Methods in it Bintang Fajar Kindergarten Palembang - Tiwi Pelayani Agustina; Mardiana Sari; Syarwani Ahmad (Journal on Education, 2024)
This study aims to find out how the project method can increase the creativity of group B children at TK IT Bintang Fajar Palembang. The location of the research was carried out at TK IT Bintang Fajar Palembang, while the school's address is at Jalan Tegal Binangun Komp Asy Syifa, Plaju Darat Village, Plaju District, Palembang City, South Sumatra Province. The subjects in this study were children of IT Bintang Fajar Palembang Kindergarten aged 5-6 years, namely 12 children consisting of 4 girls and 8 boys. The research uses quantitative and qualitative methods with an action research model according to Kemmis and Taggart which focuses on children's creativity. The results of the study were an increase in the average level of achievement of the development of group B children's creativity from pre-cycle to cycle I and to cycle II, namely that in the pre-cycle the score was 18.92 in the undeveloped category, then in cycle I with a score of 29.5 with the category that started to develop increased by 10.58 while in cycle II with a score of 41.25 with the developing category according to expectations this indicated that cycle II had an increase of 11.75, so it was concluded at the end of cycle II, the research was said to be successful because the success criteria has been reached according to the agreement of the researcher and the collaborator.